Effective Ways of Teaching English to the Young Learners - Sheraliyeva Dildora Abduvaxob kizi (Genius Journals, 2023)
Teaching English to the young generation is an area that requires special attention. This article discusses various methods, peculiarities and nuances of this field
Keywords: games; child psychology; vision